Social guidance in the letters of Saint Paul the Apostle - Ana-Maria DULEA (Diversitate si Identitate Culturala in Europa)
Paul the Apostle was very aware that the effectiveness of preaching Christian teachings depended on the practical application of these teachings in the daily lives of new converts to Christianity. He usually addressed simple people, with family issues, with socio-professional integration problems, relationships with local authorities etc. Therefore, he presents Christian dogma through the lens of their specific needs, giving them practical advice on how to conduct themselves in society, which he directly linked to divine protection if the citizens managed to behave according to the canons established by the Holy Scriptures.